EFFECT OF TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION ON POST - OPERATIVE PAIN FOLLOWING A CARDIAC SURGERY- A PILOT STUDY (International Journal of Physiotherapy, 2015)
Background: Pain has been pointed out as one of the chief concerns of patients following a cardiac surgery. Adjunctive methods of postoperative pain control that may limit narcotic side effects are of considerable interest. The study aimed to evaluate the effectiveness of Transcutaneous electrical nerve stimulation (TENS) for treatment of post-operative pain in patients who underwent cardiac surgery using a median sternotomy. In addition, we sought to compare effectiveness of TENS and SHAM (placebo) TENS on1. Pain at rest2. Duration Of analgesia following the intervention.Methods: Twenty patients (8 females and 12 males) each during the 24-96hr post-operative period were a part of the study. They were randomly allocated to two groups: TENS & pharmacological analgesia (n=10) and SHAM & pharmacological analgesia (n=10). The Visual Analogue Scale (0-10) was used to assess the post-operative peri- incisional pain.Results: It was seen that both TENS and SHAM TENS (P value is 0.0917) were almost equally effective in reducing peri- incisional pain following a cardiac surgery through a median sternotomy. However, the duration of analgesia following treatment with TENS was significantly greater than that with SHAM TENS.Conclusion: Therefore both TENS and SHAM TENS can be used as a valuable strategy to alleviate post-operative suture site pain following a cardiac surgery, both clinically and statistically, but the duration of analgesia following TENS is significantly greater than that following SHAM.